Perxis realisation as freedom and the human foundation in the context of Marx's criticism of modernity - Ali Fotutian; ُSeyyed Saeed Zahed Zahedani; Majid Movahhed Majd (حکمت اسرا)
In this paper, the central issue that is followed is the discussion of freedom and its realization from the perspective of Marx. While the central issue in modernity is the realization of human freedom, this meaning of freedom has changed and changed throughout history. However, one can argue that the central criteria for human freedom in modernity is a kind of self-determination that this criterion has been affected by various changes. The presence of the grand praxis is the ultimate outcome of freedom and history from the perspective of Marx, and history is nothing but the work of man creation, but its rising face is nothing more than society, and in this sense it is possible to emerge as a social reappearance and only a social aspect.